El retablo de Maese Federico: Lorca’s Romancero gitano as puppet theatre - Roberts, Stephen G.H. (Taylor & Francis, 2012)
This article considers the profound influence that puppet theatre had on Federico García Lorca’s poetic vision and practice at the time that he was writing the poems that would eventually make up the Romancero gitano (1928). Taking the ‘Romance sonámbulo’ as its main example and focusing on elements such as setting, stage space, lighting and décor, characterisation, movement, choreography, and the complicit relationship between puppeteer, character and audience, it shows how Lorca draws on and plays with all the machinery and conventions of puppet theatre in this collection and, to all intents and purposes, transforms each of its poems into a mini puppet play. The article ends by considering the wider consequences for our reading of the Romancero gitano of Lorca’s puppet aesthetic.